Said Nursi’s theologico-spiritual framework in Risale-I Nur: revivalism of Islamic worldview through contemporary approach - Mohd. Shahran, Mohd. Farid (2010)
It goes without saying that as a renowned religious figure of the twentieth century Bedi’uzzaman Sa’id Nursi has left a tremendous impact on different facets of Muslims’ religious life, not only in Turkey but also in other parts of the Muslim world. The substantial reform on religious understanding that he brought to the Muslims particularly in Turkey through his powerful theological and spiritual framework could serve as a good method of da’wah in general and educational approach in particular to the Muslims of other countries. This paper examines briefly how this framework of Nursi’s thought reflected in his masterpiece, Risale-i Nur could serve as a strong basis of a proper reconstruction of Islamic worldview through contemporary intellectual tool particularly the modern scientific knowledge.